Main reasons for honey bee colony mortality in Portugal. A snapshot of beekeepers' beliefs - Pires, Sancia (2014)
Since winter 2006, extensive honey bee colony losses with distinctive features were first reported in the USA ( ‘Colony Collapse Disorder’, CCD). Global research over the past few years attempting to pin point CCD’s most likely causes, recurrently pointed out that no single factor is universally responsible for this disorder. Nevertheless, stressors e.g. the Varroa mite, some ‘new generation’ pesticides, an ever expanding ‘pathosphere’ affecting European Apis mellifera strains (just to name a few) and their multiple interactions with other long ongoing stress sources clearly compromise the multi‐level immune defense of honey bees, disrupting their social system and leading colonies to collapse. In Spain, various reports have suggested that Nosema ceranae is the main culprit regarding the abnormally high colony mortality levels reported. In Portugal, no reliable information existed (other than a few discrete anecdotal reports) on honey bee colony mortality levels across the beekeeping regions of the country, nor their ‘perceived’ causes. As a result, we carried out this work focusing on narrowing this knowledge gap by getting an overview of our beekeepers opinions. This study appears in the context of a project submitted by FNAP Measure 6A National Beekeeping Program (under EU Regulations No. 917/2004, No. 797/2004 and No. 1234/2007), in partnership with research institutions of the authors, under coordination of Prof. Sância Pires.